Retrospective Effect in Islamic Criminal Law and the Federal Constitution: A Comparative Analysis: (Kesan Retrospektif Undang-Undang Jenayah Menurut Perundangan Islam dan Perlembagaan Persekutuan: Satu Analisis Perbandingan) (Kanun: Jurnal Undang-undang Malaysia, 2020)
This article comparatively analyzes the retrospective application of criminal laws between Islamic law and the Federal Constitution. Islamic law has placed two important exceptions to the retrospective application of criminal law. Firstly, if the crime is so dangerous and capable of posing a threat to public peace and the stability of the country, and secondly, if the law is in favour of the offender. This includes circumstances where a new law provides for a lighter punishment or decriminalizes the act. If the new law provides for a greater punishment then it cannot be applied retrospectively since it disfavours the offender. On the other hand, Article 7(1) of the Constitution clearly provides for only two circumstances in which criminal laws cannot be enforced with retrospective effect i.e. if the act was not a crime under the existing law at the time it was committed, and if a new law provides for a greater punishment.Keywords: ex post facto, Federal Constitution, crime cases, comparative analysis